Report of the Advisory Committee on Hirakud Dam Project March 1952 - Planning Commission (Planning Commission, 1952)
The Hirakud Dam Project, which was originally estimated to cost Rs. 47.8 crores was sanctioned by the Government of Orissa in April 1948. On account of general rise in prices both in India and abroad, devaluation of the rupee, increase in labour wages, and extension of the scope of the project, the original project estimate had to be revised, cost of which amounted to Rs. 89.09 crores.
Government of India, Central Water and Power Commission